INFORMATION TECHNOLOGIES IN TEACHING ENGLISH AS A FOREIGN LANGUAGE IN THE EDUCATION OF THE UNITED STATES OF AMERICA - Zubenko, Т. В. (Journal of Information Technologies in Education (ITE), 2018)
In the article the author examines and analyzes the information technologies created by American scholars to improve the ways and means of teaching English as a foreign language within the “AE E-Teacher Program”, developed under the leadership of the nonprofit human development organization “FHI 360” (Family Health International 360) with the aim of improving English language acquisition, providing access to a variety of authentic materials that are relevant to the most important issues of the development of the foreign language teaching methodology in international education and the needs of mankind. The exclusive right to teach this program was given to the Iowa State University. After taking the full course of it, the author of the article gives a description of existing Internet tools, resources and software in language teaching, describes the feasibility of their use for solving the didactic tasks of the lesson in teaching listening, reading, speaking, writing, grammar and vocabulary of English as a foreign language. The researcher also outlines the needs of Ukrainian teachers in creating a database of modern technologies that provide updated materials related to modern life, different types of speech activities for students with different levels of knowledge; methodological elaborations proposed by scholars and practitioners, technologies that are capable of replacing fast-paced textbooks, enhance students’ motivation and interest in learning.